The Ustilago maydis ubc4 and ubc5 Genes Encode Members of a MAP Kinase Cascade Required for Filamentous Growth - David L. Andrews; John D. Egan; María E. Mayorga; Scott E. Gold (Molecular Plant-Microbe Interactions, 2000)
Ustilago maydis, the causal agent of corn smut disease, displays dimorphic growth in which it alternates between a budding haploid saprophyte and a filamentous dikaryotic pathogen. We are interested in identifying the genetic determinants of filamentous growth and pathogenicity in U. maydis. To do this we have taken a forward genetic approach. Earlier, we showed that haploid adenylate cyclase (uac1) mutants display a constitutively filamentous phenotype. Mutagenesis of a uac1 disruption strain allowed the isolation of a large number of budding suppressor mutants. These mutants are named ubc, for Ustilago bypass of cyclase, as they no longer require the production of cyclic AMP (cAMP) to grow in the budding morphology. Complementation of a subset of these suppressor mutants led to the identification of the ubc4 and ubc5 genes, which are required for filamentous growth and encode a MAP (mitogen-activated protein) kinase kinase kinase and a MAP kinase kinase, respectively. Evidence suggests that they are important in the pheromone response pathway and in pathogenicity. These results further support an important interplay of the cAMP and MAP kinase signal transduction pathways in the control of morphogenesis and pathogenicity in U. maydis.